Integrated motor drives - Deng, Xu; Mecrow, Barrie (IET energy engineering series, 2022)
To optimise the efficiency of electric drives it is necessary to consider the components; the power electronic converter, the electric machine and the gearbox, together. Integrated systems can be smaller and have better flexibility and thermal management. Integrated motor drives (IMDs) specifically offer advantages including lower cost of installation and higher power density. This integration concept has been adopted in various electrical machine drive systems as well as electric vehicles. Integrated Motor Drives presents the state of research and future trends in integrated electrical motor drive technology and helps readers fill gaps in their knowledge. Chapters cover electrical machines, power converters and control techniques, adoption of wide bandgap semiconductor switching devices, thermal management, passive devices, gearboxes, research prototypes and commercial products, as well as emerging technologies and needs. This book for electrical motor drive engineers and researchers in academia and industry, as well as advanced students and experts, is systematically written by members from leading working groups. Close collaboration between chapter authors improves cohesion and usability for advanced students.